Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.21873/invivo.11517
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced Oral Mucositis in Brazilian Patients: Prevalence and Associated Factors

Abstract: Aim: To determine the prevalence of radiationinduced oral mucositis (OM) and associated factors. Patients and Methods: A cross-sectional retrospective study was performed at a reference dental care center. The medical records of patients submitted to radiotherapy for the treatment of head and neck cancer were used to collect clinical and demographic variables. The data were submitted to descriptive analysis and multivariate Poisson regression with robust variance [p<0.05; 95% confidence intervaI (CI)]. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 29 publications
(32 reference statements)
1
15
0
5
Order By: Relevance
“…Dentro desse âmbito epidemiológico, nota-se que o percentual de pacientes afetados aumenta para cerca de 60-85% em indivíduos submetidos a transplantes de células tronco-hematopoiéticas. Ao verificar essa manifestação em pacientes que realizam a quimioterapia adjuvante, a mucosite em relação aos pacientes que não realizaram esse procedimento, foi 50% maior (Morais et al, 2015;Sonis, 2009;Pereira et al, 2019).…”
Section: A Mucosite Oralunclassified
See 1 more Smart Citation
“…Dentro desse âmbito epidemiológico, nota-se que o percentual de pacientes afetados aumenta para cerca de 60-85% em indivíduos submetidos a transplantes de células tronco-hematopoiéticas. Ao verificar essa manifestação em pacientes que realizam a quimioterapia adjuvante, a mucosite em relação aos pacientes que não realizaram esse procedimento, foi 50% maior (Morais et al, 2015;Sonis, 2009;Pereira et al, 2019).…”
Section: A Mucosite Oralunclassified
“…Ao analisar o panorama geral das manifestações oncológicas frente ao gênero, questões como péssimos hábitos de higiene e autocuidado, além de uma menor busca por serviços de saúde bucal, podem influenciar na manifestação da mucosite oral em pacientes do sexo masculino (Pereira et al, 2019). Contudo, frente à neoplasia da mama, fica explícito que as pacientes do sexo feminino possuem mais chances de manifestar essa reação adversa devido à alta incidência desse tipo de câncer nessa população (Araújo et al, 2015).…”
Section: A Mucosite Oralunclassified
“…However, normal cells are also affected by head and neck radiotherapy, which can cause salivary gland dysfunction and, consequently, hyposalivation that dramatically increases the risk for dental caries. Furthermore, radiotherapy also causes some damage to the dental hard tissue, increasing its susceptibility to demineralization 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the effective approaches to maintain oral health is oral care, which has been evidenced to maintain oral health by reducing bacteria in the oral cavity [ 2 ]. As routine care, oral care is an effective measure to reduce the risk for infection [ 3 ], decrease the incidence of pneumonia [ 4 ], prevent the occurrence of mucositis [ 5 ] and significantly improve the quality of life of the patient [ 3 ]. It has been reported that approximately one in ten cases of death caused by pneumonia in residents of nursing homes for the elderly could be prevented by improving oral hygiene [ 6 ].…”
Section: Introductionmentioning
confidence: 99%